Job characteristics and staying engaged in work of nurses: Empirical evidence from Malaysia - Noraini Othman; Aizzat Mohd Nasurdin (International Journal of Nursing Sciences, 2019)
Objective: The purpose of this study is to examine the relationship between job characteristics (job autonomy, job feedback, skill variety, task identity, task significance) and work engagement of nurses in Malaysia. Methods: A survey using self-administered questionnaires was used to collect data from a sample of 856 staff nurses working in eight public hospitals in Malaysia. A shortened nine-item version of the Utrecht Work Engagement Scale(UWES-9) was used to measure work engagement. The UWES-9 comprises three dimensions, which was measured with three items each: vigor, dedication, and absorption. Job characteristics (job autonomy, job feedback, skill variety, task identity, task significance) were measured with the corresponding subscales of the Job Diagnostic Survey. Each subscale consisted of three items. Hypotheses were tested using hierarchical regression analysis. Results: Findings indicated that all the five demographic variables (age, marital status, education, organizational tenure, job tenure) were unrelated to work engagement. The results further revealed that job autonomy (β = 0.19, P < 0.01), job feedback (β = 0.10, P < 0.01), task identity (β = 0.13, P < 0.01), and task significance (β = 0.08, P < 0.05) were positively related to work engagement. Skill variety (β = 0.03, P > 0.05), however, did not affect work engagement. Conclusion: Job autonomy, job feedback, task identity, and task significance are important factors in predicting work engagement. The findings of this study highlighted the need to incorporate these core dimensions in nursing management to foster work engagement. Keywords: Hospitals, Job characteristics, Malaysia, Nursing staff, Work engagement